MCM10 expression is linked to cervical cancer aggressiveness - Ahmed, Sumayyah M. Q.; Laha, Suparna; Das, Ranajit; Ifthikar, Mariam Anjum; Das, Shankar Prasad (Frontiers in Molecular Medicine, 2023)
Cervical cancer is one of the major cancer types affecting women worldwide. Early detection of cervical cancer is still a challenge due to a lack of suitable biomarkers and the absence of routine checkups. One of the potential biomarkers being exploited are the minichromosome maintenance proteins (MCMs), which show both specificity and sensitivity. MCM2-7 are involved in the regulation of DNA replication and the MCM subunits are highly expressed in malignant tissues. Unlike other MCMs, MCM10, which is not part of the core helicase complex, is a critical determinant of origin activation and its levels are limiting in cancer cells. In this study, we performed bioinformatic analysis on the expression profile of all DNA replication associated MCM proteins in cervical cancer. MCM10 showed a relatively higher expression profile compared to the other MCMs. The mRNA expression levels of the MCMs were significantly increased in tumour tissues compared to normal, and MCM10 showed a fold change of 3.4. In order to understand if MCM10 is associated with the aggressiveness of cervical cancer, we looked into the mRNA expression pattern of MCM10 in three cervical cell lines. MCM10 expression was significantly higher in the case of the more aggressive cancer cell line Hela compared to controls. MCM10, therefore, can serve as a prominent biomarker for cancer progression and thus aid in early detection to control the spread of cancer cells. Our results show that MCM10 expression levels in cervical cancer cell lines are associated with cancer aggressiveness, demonstrating its clinical significance.